Jenis-Jenis Jamur Entomopatogen Dalam Usus Rayap Pekerja Coptotermes curvignathus Holmgren - Riza Linda, Sekar Puri Indria, Siti Khotimah, (Jurnal Protobiont, 2013)
Entomopathogenic fungi can be developed as pest termites control that are environmentally friendly. The aim of this research was to determine the types of entomophatogenic fungi that were isolated from Coptotermes curvignathus Holmgren worker termite gut. This research has been done from April to July 2013. Termites C. curvignathus were collected from Arboretum area on Faculty of Forestry in Tanjungpura University Pontianak. Isolation were done in 10 worker termite's guts using direct planting method. This research obtained 3 genus of fungi namely: Aspergillus, Curvularia and Penicillium, two of them can be used as entomophatogenic fungi, namely Aspergillus and Penicillium.